Planning Workshop: Building A Covid-19 Rapid Response & Agricultural-Foresight Department In Egypt: Building the Digital Transformation Unit of the Ministry of Agriculture and Land Reclamation - El Kersh, Mohamed (2021)
The online start-up workshop presented the "Building a COVID-19 Rapid Response and Ag-Foresight Department in Egypt" project’s activities and future plans, including collaborative discussion and brainstorming with stakeholders on the most relevant issues and policies in the agricultural sector’s resilience during COVID-19.